Bilingualism versus monolingualism and its correlation with the interpreting mode - Vertanová, Silvia; Slobodová, Monika (Círculo de Lingüística Aplicada a la Comunicación, 2020)
The article presents results of a research in the field of professional interpreters, specifically concerning the existence of a correlation between bilingualism/monolingualism and personal preferences for consecutive or simultaneous interpreting mode.  The results reveal that such correlation is statistically significant. In particular, it was found that professional bilingual interpreters prefer consecutive interpreting, while professional monolingual interpreters prefer simultaneous interpretation. Based on the information, specific didactic activities should be elaborated and included in the university training process for future interpreters who are usually mostly monolingual. In addition, to strengthen the cultural immersion of interpretation students, it is advisable to comprise also public speaking classes in the target language and anti-stress exercises among interpreters´ training activities.
Keywords: personal affinity; type of bilingualism of the interpreter; simultaneous mode; consecutive mode